Påverkar inavelsgraden hovbroskförbening och prestation hos kallblodstravare? - Snöberg, Gabriella (SLU/Dept. of Anatomy, Physiology and Biochemistry (until 231231), 2019)
Sidebone is considered as a disease and is regulated in horse breeding according to the Swedish animal welfare law. Cold-blooded trotter stallions with sidebones are not allowed to be used in breeding. The population of the cold-blooded trotters is relatively small and the risk of inbreeding increases when fewer number of stallions are approved for breeding. Studies have shown that sidebones do not result in any reduction in performance during competition.